2013
DOI: 10.5194/tc-7-1721-2013
|View full text |Cite
|
Sign up to set email alerts
|

Potential subglacial lake locations and meltwater drainage pathways beneath the Antarctic and Greenland ice sheets

Abstract: Abstract. We use the Shreve hydraulic potential equation as a simplified approach to investigate potential subglacial lake locations and meltwater drainage pathways beneath the Antarctic and Greenland ice sheets. We validate the method by demonstrating its ability to recall the locations of > 60 % of the known subglacial lakes beneath the Antarctic Ice Sheet. This is despite uncertainty in the ice-sheet bed elevation and our simplified modelling approach. However, we predict many more lakes than are observed. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
125
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(139 citation statements)
references
References 53 publications
14
125
0
Order By: Relevance
“…The presence of at least some localised patches of high abruptness in thawed regions is consistent with the recent discovery of two small subglacial lakes in north-western Greenland of ∼ 8 and ∼ 10 km 2 in extent (Palmer et al, 2013). More generally, however, the relative rarity of high abruptness in thawed regions is in agreement with hydrological potential analysis (Livingstone et al, 2013), which predicts that deep subglacial lakes are both rare and small in the north-west of the GrIS. Instead, channelised drainage networks -such as the system recently identified beneath Humboldt glacier (Livingstone et al, 2017) -are likely to be common in thawed regions (and are consistent with the generally diffuse scattering signature that we observe).…”
Section: Discussionsupporting
confidence: 75%
“…The presence of at least some localised patches of high abruptness in thawed regions is consistent with the recent discovery of two small subglacial lakes in north-western Greenland of ∼ 8 and ∼ 10 km 2 in extent (Palmer et al, 2013). More generally, however, the relative rarity of high abruptness in thawed regions is in agreement with hydrological potential analysis (Livingstone et al, 2013), which predicts that deep subglacial lakes are both rare and small in the north-west of the GrIS. Instead, channelised drainage networks -such as the system recently identified beneath Humboldt glacier (Livingstone et al, 2017) -are likely to be common in thawed regions (and are consistent with the generally diffuse scattering signature that we observe).…”
Section: Discussionsupporting
confidence: 75%
“…This is in agreement with previous studies, which have also found a potential for changes in drainage pattern (Livingstone et al, 2013;Christianson et al, 2014).…”
Section: Subglacial Water Outfluxsupporting
confidence: 83%
“…5b) the water routeways can be seen to pool together in the southeastern part of the drainage basin, indicating the possibility of subglacial lakes. Their positions correspond largely to areas identified by Livingstone et al (2013) as potential lake locations. However, the areas likely to contain subglacial lakes in our study coincide not only with areas where the bed slope is equally or more important than the surface slope, but also with areas where the error in bed rock topography is upwards of 300 m (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Streamlines derived from the hydraulic potential gradient map pass though the lakes. The lakes are also located on a "potential subglacial lake" area, identified from previous analysis of continent-wide subglacial hydraulic potential (Livingstone et al, 2013). Figure 4 shows the elevation and volume changes of three SGLs, representing sequential filling events in 2013.…”
Section: Hydrological Connectivity Of Subglacial Lakes In the Kamb Icmentioning
confidence: 99%